Spatial analysis of Varroa destructor and the relationship with surrounding landscape types in Southern Ontario - Sobkowich, Kurtis Edward; Berke, Olaf; Bernardo, Theresa M.; Pearl, David L.; Kozak, Paul (Frontiers in Ecology and Evolution, 2022)
Elevated colony losses have continued to be an issue for Canadian beekeepers for more than a decade. Numerous studies have identified unmanaged Apis mellifera colony infestation by the Varroa destructor mite as a main cause of the problem. V. destructor spread externally of the hive through a phoretic stage in their life cycle. Consequently, their movement outside the hive is influenced by honey bee flight behaviours, which can range to multiple kilometers from the originating hive in any direction. V. destructor are therefore of regional concern as neighboring colonies and yards share nearby forage which can serve as fomites. Additionally, mites can be transmitted through bee behaviours such as robbing and drifting, thus impacting surrounding colonies. Understanding the distribution of mites across a population is key for surveillance and equitable allocation of resources. Spatial patterns of V. destructor infestations in Southern Ontario, Canada, were investigated using a combination of cluster analysis, scan statistics, and geostatistical modelling, using five years of provincial apiary inspection data, from 2015 to 2019. A collection of disease clusters of V. destructor infestations was identified and found to be stable over multiple years with several other individual clusters occurring sporadically throughout Southern Ontario during the same study period. Universal kriging was applied to the V. destructor data in combination with regional colony density, and land use data as covariates, producing an isopleth map of the prevalence risk for V. destructor infestation. No substantial link between V. destructor infestation and environmental factors was found. This study highlights the need for more data and investigation to determine the cause of the identified clusters and areas of elevated risk. These results are hypothesis-generating but simultaneously provide information for government agencies, industry organizations, and beekeepers into the spatial distribution of V. destructor at a macro scale.